2010
DOI: 10.1200/jco.2009.27.6774
|View full text |Cite
|
Sign up to set email alerts
|

Are Mastectomy Rates Really Increasing in the United States?

Abstract: In contrast to single-institution studies, our population-based analysis found a decrease in unilateral mastectomy rates from 2000 to 2006 in the United States. Variations in referral patterns and patient selection are potential explanations for these differences between single institutions and national trends.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
156
4
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(171 citation statements)
references
References 24 publications
9
156
4
2
Order By: Relevance
“…A similar rate of 37% was reported from USA SEER data for [2000][2001][2002][2003][2004][2005][2006], although this applied to combined ductal carcinoma in situ and AJCC TNM stages I to III invasive cancers, whereas our data were for invasive cancers classified using the NHMRC definition of early invasive breast cancer (i.e., tumours <50mm in size and without fixed nodes or distant metastases) (National Breast Cancer Centre, 2001;Cuncins-Hearn et al, 2006;Habermann et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A similar rate of 37% was reported from USA SEER data for [2000][2001][2002][2003][2004][2005][2006], although this applied to combined ductal carcinoma in situ and AJCC TNM stages I to III invasive cancers, whereas our data were for invasive cancers classified using the NHMRC definition of early invasive breast cancer (i.e., tumours <50mm in size and without fixed nodes or distant metastases) (National Breast Cancer Centre, 2001;Cuncins-Hearn et al, 2006;Habermann et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Statement and reviews of evidence from randomized trials (Abrams et al, 1995;Fisher et al, 1995), mastectomy rates declined markedly in the U.S. (Lazovich et al, 1991;Lazovich et al, 1997;Habermann et al, 2010), Canada, (Gaudette et al, 2004) European countries, (Zorzi et al, 2006), although with a more recent upturn suggested in some North American localities (Tuttle et al, 2007;Katipamula et al, 2009;Dragun et al, 2012a;2012b). Australian data also showed a trend away from mastectomy towards breast conserving surgery both nationally and in a number of jurisdictions (Hill et al, 1990;1994;Byrne et al, 1993;South Australian Cancer Registry, 2000;Cuncins-Hearn et al, 2006;Kricker, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The justification of this increase was related to the use of MRI of the breast 23 and greater liberality in conducting prophylactic operations 25 . Studies using population-based cancer registries showed reduction of mastectomies in the United States 25 , Norway 26 and Spain 27 , though. During the study period our patients did not have access to breast MRI; prophylactic mastectomy, although described in our protocol, has hardly been used.…”
Section: Discussion Discussion Discussion Discussionmentioning
confidence: 99%
“…These days standard practice is breast conserving surgery followed by adjuvant radiotherapy for early presentation [1] and mastectomy followed by adjuvant radiotherapy of the chest wall with or without chemotherapy in advanced cases [2]. Many studies [3,4] have shown that adjuvant radiotherapy to the chest wall improves local control and also survival in node positive and advanced node negative breast cancer patients after mastectomy.…”
Section: Introductionmentioning
confidence: 99%